Speaking in Tongues: Margaret Laurence’s A Jest of God as Gothic Narrative - Stein, Karen (Studies in Canadian Literature, 1995)
Margaret Laurence’s A Jest of God has strong affinities to Claire Kahane’s analysis of the Gothic narrative tradition: these include the supernatural, sleep-like states, difficulties in telling a story, discovery of secrets, discussions of female sexuality, absent mothers, a secret room, a controlling male figure, a mysterious lover, and different narrative voices. Gothic novels also explore the position of women in the home and family. Laurence incorporates Gothic conventions but modifies them, allowing her heroine, Rachel, to find her own voice(s) and escape from the guilt, shame, and imprisonment of her past.